Stent Retriever or Aspiration Catheter Alone vs Their Combination as the First-Line Thrombectomy in Acute Stroke. Issue 1 (26th January 2023) - Ohta, Tsuyoshi; Tanaka, Kanta; Koge, Junpei; Yoshimoto, Takeshi; Kushi, Yuji; Shiozawa, Masayuki; Inoue, Manabu; Satow, Tetsu; Iihara, Koji; Ihara, Masafumi; Koga, Masatoshi; Toyoda, Kazunori; et al.
Abstract : BACKGROUND: The single-device simplicity for mechanical thrombectomy (MT) is now challenged by the complementary efficacy of dual-device first-line with a stent retriever and an aspiration catheter. OBJECTIVE: To compare the outcomes after MT initiated with a single device vs dual devices in acute anterior circulation large vessel occlusion. METHODS: Patients who underwent MT for acute internal carotid artery (ICA) or M1 occlusion between 2015 and 2020 were retrospectively analyzed. We divided patients into 2 groups: single-device first-line, defined as patients who underwent first-device pass with either a stent retriever or aspiration catheter, and dual-device first-line, defined as first-device pass with both devices. RESULTS: One hundred forty-one patients were in the single-device group, and 119 were in the dual-device group. In the dual-device group, coiling or kinking of the extracranial ICA was more frequent ( P = .07) and the guide catheters were less frequently navigated to the ICA ( P < .001). 37% of the single-device group was converted to dual-device use. The proportions of mTICI ≥ 2c after the first pass were similar (33% vs 32%. adjusted odds ratio 0.91, 95% CI 0.51-1.62). An mRS score of 0 to 2 at 3 months was achieved similarly (53% vs 48%, P = .46). The total cost for thrombectomy devices was lower in the single-device group ( P < .001). CONCLUSION: The proportions of first-pass mTICI ≥ 2c were not different between the 2 groups with similar functional outcomes, although the dual-device group more likely to have unfavorable vascular conditions.